Psychosis and Dandy-Walker syndrome: a case report and review of the literature. Issue 2 (14th April 2021) - Porras Segovia, Alejandro; Guerrero-Jiménez, Margarita; Carrillo de Albornoz Calahorro, Carmen Maura; Gutierrez-Rojas, Luis
Abstract : Dandy-Walker syndrome (DWS) is a group of brain malformations which sometimes present with psychotic symptoms. We present the case of a patient diagnosed with Dandy-Walker variant who presented with schizophrenia-like psychosis. A man in his 30s was admitted to an acute psychiatric unit presenting with persecutory delusions, auditory hallucinations and violent behaviour. The MRI performed showed the typical alterations of Dandy-Walker variant: vermian hypoplasia and cystic dilatation of the fourth ventricle. He also suffered from mild intellectual disability. After being treated with olanzapine 10 mg/d for a month, his psychotic symptoms greatly improved and he was discharged. In conclusion, DWS may cause psychosis through a dysfunction in the circuit connecting prefrontal, thalamic and cerebellar areas. The association between these two conditions may contribute to the understanding of the aetiopathogenesis of schizophrenia.